Le monde en plus étrange : à propos du concept d’« estrangement » en théorie de la science-fiction - Simon Spiegel (ReS Futurae)
The concept of “estrangement” has been central to sf criticism ever since Darko Suvin defined the genre as creating the effect of "cognitive estrangement". By going back to the theories of Viktor Shklovsky and Bertolt Brecht, I will show how Suvin, in his approach, intermingles formal, fictional, generic, and receptive aspects of estrangement. Contrary to Suvin’s assessment, it is not sf’s primary formal operation to render familiar things strange, but to make the alien look ordinary, a process I call naturalization. In sf, estrangement mainly happens on a diegetic level, when a marvelous element is introduced into an apparently realistic world.